Access to essential medicines in low-resource settings: a systematic review - Bhanja, Mrutyunjaya; Vaishnaw, Aayush (Journal of Neonatal Surgery, 2025)
Almost 2 billion people worldwide lack access to necessary medications. This indicates that for over 25% of the global population, vital medications are either inaccessible, unaffordable, unsatisfactory, or of poor quality. By presenting fresh research findings from low- and middle-income countries (LMICs), this supplement illustrates the consequences of inadequate access to medications and emphasizes contemporary solutions to increase access to vital medicines. These research provide answers to important concerns like: Can performance-based financing increase access to necessary medications? How much do pediatric cardiovascular therapies cost? Which nations' legal systems support widespread access to pharmaceuticals? To what extent do people use medications appropriately? Does equity suffer from subpar medications? Since critical medications are key to the Sustainable Development Goals and central to the pursuit of Universal Health Coverage, the answers to these concerns are crucial. In order to lower the cost of care, avoid increased pain and suffering, decrease the length of sickness, and prevent unnecessary impairments and deaths globally, access to reasonably priced, high-quality vital medications is needed. Health Systems Global's Medicines in Health Systems Thematic Working Group, a membership organization devoted to advancing health systems research and knowledge translation, developed this supplement. By highlighting recent achievements and difficulties in expanding access to quality-assured medications through health systems in LMICs, the five papers in the supplement deepen our understanding.